PENGARUH TEPUNG LIMBAH TEGEL KERAMIK SEBAGAI FILLER TERHADAP PERMEABILITAS ADUKAN - Lilik Hariyanto, V. (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This research aimed to investigate the permeability of mortar mixed with ceramic tile powder, in order to find alternative filler material that can slow the permeability speed of mortar. This experimental research used 120 samples in four categories of filler composition (0%, 35 %,37.5 % and 40 %). Mortar with composition of 1 cement : 4 sand : 0 ceramic tile powder (by weight) was used as control variable. Descriptive and statistical methods were used to analyse the results of this research. The statistical analysis includes the value of mean (M) and standard deviation (SO). From the results, it can be concluded that there were significant differences regarding the value of permeability among the composition variations. The maximum permeability could be reached by the mortar with composition of 1 cement : 4 sand : 35 % ceramic tile powder and followed by the mortar with composition of 1 cement: 4 sand: 37.5 % ceramic tile powder and 1 cement: 4 sand: 40% ceramic tile powder. Keyword: mortar filler, ceramic file powder, permeability